2020
DOI: 10.1186/s12978-020-00938-3
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child sexual and reproductive health communication among very young adolescents in Korogocho informal settlement in Nairobi, Kenya

Abstract: Background Parents are an important source of sexual and reproductive health (SRH) information for very young adolescents and are likely to have a significant influence on adolescents’ sexual attitudes, values, and risk-related beliefs. This study explored the nature and content of parent-child communication about SRH issues. Methods Thirty-two parents and 30 adolescent boys and girls aged between 11 and 13 years participated in narrative interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 51 publications
5
37
1
1
Order By: Relevance
“…For example, a VYA who is sexually active and seeking knowledge on how to protect herself from a negative SH consequence is unlikely to approach her parents or elder relatives if they had previously discouraged sexual relationships. This finding is in line with that of a study conducted among VYAs in Kenya where adolescents were discouraged from revealing their sexual or romantic connections because they were afraid of negative parental reactions if they disclosed their engagement or interest in romantic partnerships (50).…”
supporting
confidence: 90%
“…For example, a VYA who is sexually active and seeking knowledge on how to protect herself from a negative SH consequence is unlikely to approach her parents or elder relatives if they had previously discouraged sexual relationships. This finding is in line with that of a study conducted among VYAs in Kenya where adolescents were discouraged from revealing their sexual or romantic connections because they were afraid of negative parental reactions if they disclosed their engagement or interest in romantic partnerships (50).…”
supporting
confidence: 90%
“…Boys, on the other hand, demonstrated an increased perceived severity and thought the 24-hour news medium was increasing their stress. In previous literature, sources of information for girls include parents and internet [ 23 , 24 ]. Burnout due to information overload from social media, specifically in relation to COVID-19, has also been documented within the literature but differences by sex have not been investigated [ 12 - 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that caregiver-to-patient and parent-to-child communication, in particular, hold the greatest potential in helping women making informed decisions about their health [ 12 , 13 ] and fostering contraceptive use [ 14 ]. However, these communication venues might be impractical when cultural norms and taboos within families are a barrier to effective communication [ 12 , 15 ]. In these situations, passive communication technologies, like TV or radio, or active communication technologies, like mobile phones, act as enablers or alternative sources of information, especially for younger people [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%